The Next Rural Economies Constructing Rural Place in Global Economies - Halseth, Greg (CABI, 2014)
The Next Rural Economiesbrings together rural and small-town scholars from seven OECD countries to present essays on the possible futureof rural development. Past approaches to rural development have tended to focus on the “space economy,” implying attention to comparative advantages, natural-resource endowments, and development strategies that sought mainly to overcome the cost of distance. Through the cumulative efforts of rural development practitioners and researchers, this space-based approach is being challenged and complemented by a recognition of the growing importance of “place-based economies.” A place-based approach to rural development means that the unique attributes and assets of individual communities and regions now underscore their attractiveness for particular and contextually appropriate types of activities and investments. The dynamics and functional attributes of place provided the purpose and substance of a workshop held in the spring of 2008 at the University of Northern British Columbia, “Space to Place: The Next Rural Economies.” The participants all shared a common focus in their work on rural community and regional development, and the workshop provided a framework for sharing and advancing our understanding of place-based approaches to rural development. The production of this volume was a key workshop objective from the outset, allowing us to identify core themes for participants to reference in their chapters (see below). This continuity of purpose and reflection facilitated a robust comparative treatment of the rural experience in each country setting.